Modelling the surface roughness behaviour of an EDMed workpiece with different tool electrodes using DoE - Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Mohammad , Yeakub Ali; M A, Mohammad Hambiyah (2013)
Surface roughness of a workpiece is one of the measures used in evaluating the performance of any machining technique. In this paper, the behaviour of a post-EDM roughness of mild steel material subjected to machining with two different electrodes is evaluated through modelling using three machining variables. The variables are peak current, pulse on-time and pulse off-time, while the electrodes used are Cu-TaC compact green electrode and metallic Cu. The investigation was planned and analysed with Design of Experiment (DoE) in which the output response obtained with the two electrodes were compared. Results indicate that the roughness obtained with Cu-TaC electrode is a function of peak current, pulse on-time, pulse off-time with interaction between on-time and off time, whereas that of metallic Cu electrode is related with current and pulse on-time only. Further more, the metallic Cu electrode produced comparatively lower roughness under all the machining conditions. The lowest roughness obtained with Cu-TaC electrode is over 100% higher than that of Cu-electrode.